Komunikasi Finansial Generasi Sandwich Pada Pasangan Suami Istri - Indah Gita Cahyani; Yanto Yanto; Anis Endang SM (Universitas Dehasen Bengkulu, 2024)
Research purposes to find out how the sandwich generation communicates and how they manage finances among married couples in Bengkulu City. Data collection methods use interviews, observation and documentation. Financial needs are indeed important for everyone, especially for the sandwich generation. This generation has to bear financial burdens which are not only used to support themselves and their children but also with their parents. They need to know how to properly manage the sandwich generation's finances so they can achieve financial independence. The results obtained from this researcher found that the financial management of the sandwich generation can be differentiated based on their work in this research, namely the type of employee, trader, freelancer, to meet the financial needs of the three generations, they work together to manage their finances so that their expenses are balanced and not too heavy and they try as hard as possible. to seek to fulfill their needs in any circumstances by communicating well and openly with each other